The Impact of Sleep Disorders on Amyotrophic Lateral Sclerosis: A Systematic Review - Bella Sugih Laksono; Nasyifa Nurul Fitriany; Iklima Fauzi Yazidah; Zam Zanariah; Nadia Amrin (The Indonesian Journal of General Medicine, 2025)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is increasingly recognized as a multisystem neurodegenerative disorder where sleep disturbances are highly prevalent and clinically significant. This review aims to systematically evaluate the evidence on the impact of various sleep disorders on the pathophysiology, clinical progression, survival, and quality of life in patients with ALS. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for observational studies, interventional trials, and meta-analyses published up to September 2024, in accordance with PRISMA guidelines. Studies assessing subjective or objective sleep parameters in ALS patients and their association with clinical outcomes were included. Methodological quality was assessed using the Newcastle-Ottawa Scale for observational studies and the Cochrane Risk of Bias tool for randomized trials. Results: Seventeen studies met the inclusion criteria. The prevalence of poor subjective sleep quality (Pittsburgh Sleep Quality Index > 5) ranged from 50% to 63%. Insomnia, sleep-disordered breathing (SDB), and restless legs syndrome (RLS) were also highly prevalent. Polysomnography (PSG) consistently revealed significant reductions in total sleep time and sleep efficiency, altered sleep architecture with decreased slow-wave and REM sleep, and evidence of nocturnal hypoxemia. Sleep parameters were significantly associated with critical clinical outcomes. Poor sleep quality was linked to a more rapid decline in functional (ALSFRS-R) and respiratory (FVC) status, shorter survival, and reduced quality of life. Specific pathologies, including obstructive sleep apnea (OSA), nocturnal hypoventilation, and periodic limb movements in sleep (PLMS), were independent predictors of mortality. Emerging genetic evidence suggests a potential causal link between OSA and an increased risk of developing ALS. Discussion: The evidence supports a bidirectional model where ALS-related pathophysiology (e.g., respiratory muscle weakness, central neurodegeneration of sleep centers) disrupts sleep, and this sleep disruption, in turn, may accelerate neurodegeneration. Potential mechanisms for the latter include impaired glymphatic clearance of neurotoxic proteins, heightened systemic inflammation, and oxidative stress from intermittent hypoxia. Conclusion: Sleep disorders are an integral and prognostically significant component of ALS, not merely a secondary symptom. Their presence is associated with accelerated disease progression and reduced survival. These findings underscore the critical need for routine sleep assessment, including polysomnography, and proactive management, particularly with non-invasive ventilation (NIV), as a core component of comprehensive ALS care.